2023
DOI: 10.1186/s12888-023-04838-1
|View full text |Cite
|
Sign up to set email alerts
|

Internet addiction and mental health disorders in high school students in a Peruvian region: a cross-sectional study

Jean C. Perez-Oyola,
Dionela M. Walter-Chavez,
J. Pierre Zila-Velasque
et al.

Abstract: Objectives To determine the association between internet addiction disorder (IAD) and anxiety and depressive symptomatology in high school students in two private schools in Chiclayo, Peru, during the COVID-19 pandemic. Materials and methods Analytical cross-sectional investigation of 505 adolescents from two private schools. The dependent variables were anxiety and depressive symptomatology, measured with the Beck Adapted Depression Questionnaire … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 88 publications
(77 reference statements)
0
2
0
1
Order By: Relevance
“…Con respecto a otros hallazgos de este proyecto, se encontró un resultado similar en la predisposición de los encuestados que previo a la pandemia presentaban un uso desmedido de las TIC a mostrar síntomas de depresión y ansiedad, lo que coincide con un estudio realizado en Perú en 2021, en el que participaron estudiantes con características sociodemográficas parecidas a los participantes de esta investigación 29 .…”
Section: Resultsunclassified
“…Con respecto a otros hallazgos de este proyecto, se encontró un resultado similar en la predisposición de los encuestados que previo a la pandemia presentaban un uso desmedido de las TIC a mostrar síntomas de depresión y ansiedad, lo que coincide con un estudio realizado en Perú en 2021, en el que participaron estudiantes con características sociodemográficas parecidas a los participantes de esta investigación 29 .…”
Section: Resultsunclassified
“…In short, the integration of strategies such as a flipped classroom supported by MOOCs can be especially beneficial for primary teachers in the Lambayeque region [33]. According to [34], these methodologies not only help them improve their information literacy, that is, the capacity to identify, access, assess, and use data from a variety of sources to solve problems, reach conclusions, and communicate effectively in both digital and analog settings, but they also teach them how to adapt to a changing educational landscape and get their students ready for the 21st-century digital world.…”
Section: Use Of the Flipped Classroom And Mooc Methodology To Develop...mentioning
confidence: 99%
“…A recent study showed that 9% of adolescents, with an average age of 14.53, exhibited high levels of internet addiction, and 11% showed overuse of online games ( 6 ). Internet addiction can have severe detrimental effects on an individual’s social and physical well-being ( 7 ), including an increased risk of depression and anxiety ( 8 , 9 ), problematic behaviors ( 6 ), poorer academic performance ( 10 ), and severe sleep disorders ( 11 ), and so on. As a result, researchers have investigated various internal and external factors that influence internet addiction and have aimed to uncover its psychological mechanisms in order to develop effective interventions ( 7 , 12–14 ).…”
Section: Introductionmentioning
confidence: 99%